Characteristics of The New Material Geopolymer Binder Course Fly Ash and Bottom Ash - Saputro, Yayan Adi; Ariyanto, Ariyanto; Qomaruddin, Mochammad (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2023)
Selection of concrete specifications is something that must be done according to needs. The use of concrete as a building material is efficiency and effectiveness in terms of processing and supply. The increase in fly ash and bottom ash waste will affect new innovations for new materials in construction. The purpose of this study was to determine the characteristics of the new material geopolymer binder course fly waste and bottom ash whether it complies with standards and is suitable for use as a construction material or for making roads. This research was carried out experimentally in the laboratory to check whether the characteristics of the material used met the standards or not. The results obtained were that the best mixture for the new material was between (FA+BA) with a compressive strength of 5.15 MPa and (FA+PS) with a compressive strength of 25.6 MPa at 28 days old with a mixture composition of 1 : 1.5. As for the mixed wear value (FA+BA) has a wear value of 76% while (FA+PS) has 39% wear. The new material resulting from the wear level can be used as a base course material.